Infection risk in patients with autoimmune cytopenias and immune dysregulation treated with mycophenolate mofetil and sirolimus - Comella, Mattia; Palmisani, Elena; Mariani, Marcello; Dell’Orso, Gianluca; Licciardello, Maria; Giarratana, Maria Carla; Arcuri, Luca; Pestarino, Sara; Grossi, Alice; Lanciotti, Marina; Brucci, Giorgia; Guardo, Daniela; et al. (Frontiers in Immunology, 2024)
Introduction Autoimmune cytopenias (AICs) are a group of disorders characterized by immune-mediated destruction of blood cells. In children, they are often secondary to immune dysregulation that may require long-lasting immunosuppression. Mycophenolate mofetil and sirolimus represent two well-tolerated options to treat these disorders, often as a steroid-sparing option. However, no data are available on the infection risk for patients undergoing long-lasting treatments. Patients and methods The rate of severe infective events was calculated in episodes per 100 persons/months at risk (p/m/r) documented by the analysis of hospitalization charts between January 2015 and July 2023 of patients treated with mycophenolate mofetil or sirolimus given for isolated AIC or AICs associated with autoimmune lymphoproliferative syndrome (ALPS)/ALPS-like syndromes in two large Italian pediatric hematology units. Results From January 2015 to July 2023, 13 out of 96 patients treated with mycophenolate mofetil or sirolimus developed 16 severe infectious events requiring hospitalization. No patients died. Overall infection rate was 0.24 person/*100 months/risk (95% CI 0.09–0.3). Serious infectious events incidence was higher in patients with ALPS-like compared to others (0.42 versus 0.09; p = 0.006) and lower in patients who underwent mycophenolate treatment alone compared to those who started sirolimus after mycophenolate failure (0.04 versus 0.29, p = 0.03). Considering only patients who started treatment at the beginning of study period, overall cumulative hazard was 18.6% at 60 months (95% CI 3.4–31.4) with higher risk of infectious events after 5 years in ALPS-like patients (26.1%; 95% CI 3.2–43.5) compared to other AICs (4%; 95% CI 0–11.4; p = 0.041). Discussion To the best of our knowledge, this is the first study to describe the infectious risk related to mycophenolate and sirolimus chronic treatment in patients with AICs and immune dysregulation. Our data highlight that infection rate is very low and mainly related to the underlying hematological condition. Conclusions Mycophenolate and sirolimus represent a safe immunosuppressive therapy in AICs and immune dysregulation syndromes.